Bamboo: Diversity, Management, Utilization Pattern and its Socio-Economic Effect in Andaman and Nicobar Islands, India - Kumar, Shashi; Murti, S. H. K.; George, Rajee (Indian Forester, 2015)
Andaman and Nicobar Islands, India has 19 species of bamboo and the area available for harvesting is approximately 14000 ha spread throughout the length and breadth of the territory. The bamboo found naturally in the Islands is thin walled and hollow. There is enough demand and scope for growing thick walled solid bamboo in the Islands. The natural bamboo forests are managed scientifically as per the prescription of working plans. The aboriginal tribes living in the Islands also use bamboo for various purposes. The bamboo supports the livelihood of a section of the society involved in bamboo article manufacturing.